PRINCIPLES BUILDING TRAJECTORIES THE DEVELOPMENT PERSONNEL POTENTIAL ENTERPRISES AND THEIR IMPACT ON BUSINESS TRANSFORMATION - CHOBITOK, Viktoriya; SHEPELENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Modern business conditions present new challenges to the management of enterprises and require them to always have flexible and adaptive strategic action plans. Spending on staff development should be seen as an investment in the future and sustainable growth of the business. The development of the labor potential of modern enterprises is an extremely important area of ​​ensuring the stability of transformational processes. Highly qualified and motivated personnel are able to perform their duties effectively and efficiently, which directly affects the overall productivity of enterprises, and also, thanks to the reduction in the number of errors in work, ensures an increase in the quality of products and services. Employees with a high level of knowledge and skills are able to generate new ideas and implement innovations thanks to the use of effective and modern methods and tools, this contributes to ensuring the competitiveness of the enterprise on the market, as well as more efficient use of available resources, which ensures a reduction in production costs and an increase in profitability.In today's turbulent conditions, the development of labor potential at enterprises allows employees to quickly adapt to changes in technologies, market conditions and regulatory requirements. This ensures flexibility and adaptability of the enterprise and increases its level of stability in a changing environment. Management of enterprises investing in the development of their employees creates a positive image on the labor market, which reduces staff turnover, helps attract creative specialists and increases the value of company vacancies. Building the trajectory of labor potential development is a key factor for achieving strategic success and stable business development.The analysis of literary sources confirms that this scientific direction is quite relevant, taking into account the new requirements and possibilities of conducting business activities of enterprises and needs further development.The purpose of the article is the theoretical and methodological substantiation of the principles of building trajectories of the development of personnel potential of enterprises and their influence on the transformation of business in modern turbulent economic conditions.The development of personnel potential that meets the needs and scale of changes at enterprises is a key structural component of the implementation mechanism of the country's socio-economic development strategy. The personnel potential of enterprises is a strategic factor that determines the success of socio-economic reforms. Qualitative and quantitative characteristics of the workforce determine the possibilities of structural restructuring of the economy, diversification and expansion of production, improvement of product quality and growth of labor productivity.The personnel potential of the enterprise is a set of abilities and skills of employees that can be used in the process of achieving the strategic goals of the enterprise. The high level of skills and knowledge of the company's personnel is the basis for active development and effective achievement of the company's goals.Personnel potential also represents a qualitative and quantitative characteristic of human capital as one of the types of active resources of the enterprise. Separately, this economic category can be considered as existing and potential personnel capabilities that are already used, can be used when needed, or can be acquired when needed. The uniqueness of personnel potential is that it can constantly develop and improve, and each of the individual characteristics (knowledge, skills) can belong to one person or a group of persons as necessary.The personnel potential of a modern enterprise forms a specific structural architecture that reproduces the relationships and properties of groups of employees. The main elements of the personnel potential structure are physiological, social, intellectual and technological components. In addition, socio-demographic, personnel and, depending on the level of management at the enterprise, can be cited.The need to develop personnel potential in today's economic conditions is a necessary fact for the sustainable development of the enterprise. Solving the tasks of effective functioning and ensuring the competitiveness of enterprises is directly related to the development of their personnel potential. Unstable business conditions, competition and intensity of economic activity, increasing attention to management problems and trends, the need for modern knowledge of management and marketing, increasing the value of personnel and ensuring adequate development costs, as well as increasing the social responsibility of enterprises for the development of personnel potential - these factors determine the principles building trajectories of the development of personnel potential of enterprises and determine the level of their influence on business transformation.The principles of building human resources development trajectories are necessary and relevant tools for modern enterprises. They provide a systematic and strategic approach to personnel development, increase business competitiveness and efficiency, promote innovative development and adaptation to changes, and also have a positive impact on corporate culture and employee satisfaction. Thus, these principles play a key role in business transformation, ensuring its successful development and sustainability in dynamic market conditions.
Keywords: personnel potential; development of personnel potential; principles; influencing factors; personnel management; modern enterprises; business transformation